Profiling Student Satisfaction: Evaluating the Effectiveness of Student Affairs and Services Programs - Montano, Mary Rose; Navarro, Arman; Dasal Jr., Aveto M.; Gonzales, Ronald A.; Ilao, Jeanne Mae; Opeña, Anna Rhea C. (RSF Conference Series: Business, Management and Social Sciences, 2025)
In the evolving landscape of higher education, Student Affairs and Services (SAS) programs play a vital role in supporting holistic student development beyond academics. As institutions strive to enhance student satisfaction, assessing the effectiveness of these programs has become essential. This study aimed to evaluate student satisfaction with SAS programs at the City College of Calamba by profiling students’ demographic characteristics, identifying satisfaction levels, and exploring the relationship between these variables. Using a descriptive-correlational mixed-methods design, data were collected from 3,032 students through a self-developed survey instrument that included both quantitative Likert-scale items and qualitative open-ended questions. Spearman’s Rho was applied to determine correlations between demographic profiles (gender, year level, and academic program) and satisfaction levels, while thematic analysis was used for qualitative data. Findings revealed that students were generally satisfied with SAS programs, particularly in areas related to student governance support and extracurricular activities. However, issues such as limited access to technological resources, financial constraints, and mental health challenges were prominent concerns. No significant relationships were found between demographic variables and satisfaction levels, indicating a broadly uniform perception of services across different student groups. The study contributed a data-driven enhancement plan focused on student-centered improvements, including expanded digital access, streamlined administrative processes, mental health initiatives, and mechanisms for amplifying student voices. These findings emphasize the importance of continuous assessment, inclusive practices, and responsive strategies in strengthening SAS programs and enhancing the overall student experience in higher education.